A genetic screen for dominant chloroplast reactive oxygen species signaling mutants reveals life stage-specific singlet oxygen signaling networks - Lemke, Matthew D.; Woodson, Jesse D. (Frontiers in Plant Science, 2024)
Plants employ intricate molecular mechanisms to respond to abiotic stresses, which often lead to the accumulation of reactive oxygen species (ROS) within organelles such as chloroplasts. Such ROS can produce stress signals that regulate cellular response mechanisms. One ROS, singlet oxygen ( 1 O2), is predominantly produced in the chloroplast during photosynthesis and can trigger chloroplast degradation, programmed cell death (PCD), and retrograde (organelle-to-nucleus) signaling. However, little is known about the molecular mechanisms involved in these signaling pathways or how many different signaling 1 O2 pathways may exist. The Arabidopsis thaliana plastid ferrochelatase two (fc2) mutant conditionally accumulates chloroplast 1 O2, making fc2 a valuable genetic system for studying chloroplast 1 O2-initiated signaling. Here, we have used activation tagging in a new forward genetic screen to identify eight dominant fc2 activation-tagged (fas) mutations that suppress chloroplast 1 O2-initiated PCD. While 1 O2-triggered PCD is blocked in all fc2 fas mutants in the adult stage, such cellular degradation at the seedling stage in only two mutants. This differential blocking of PCD suggests that life-stage-specific 1 O2-response pathways exist. In addition to PCD, fas mutations generally reduce 1 O2-induced retrograde signals. Furthermore, fas mutants have enhanced tolerance to excess light, a natural mechanism to produce chloroplast 1 O2. However, general abiotic stress tolerance was only observed in one fc2 fas mutant (fc2 fas2). Together, this suggests that plants can employ general stress tolerance mechanisms to overcome 1 O2 production but that this screen was mostly specific to 1 O2 signaling. We also observed that salicylic acid (SA) and jasmonate (JA) stress hormone response marker genes were induced in 1 O2-stressed fc2 and generally reduced by fas mutations, suggesting that SA and JA signaling is correlated with active 1 O2 signaling and PCD. Together, this work highlights the complexity of 1 O2 signaling by demonstrating that multiple pathways may exist and introduces a suite of new 1 O2 signaling mutants to investigate the mechanisms controlling chloroplast-initiated degradation, PCD, and retrograde signaling.